Integrasi Teknologi Tepat Guna dan Sistem IoT untuk Pemberdayaan Petani Jamur Tiram Dataran Rendah di Kabupaten Maros - Irmawati; Pangerang, Fitriaty; Yuniarti (Jurnal Pengabdian UNDIKMA, 2026)
This community service program aims to enhance oyster mushroom production capacity through the application of appropriate technology in the form of a gas-fueled automatic steamer, a semi-automatic baglog press, and an Internet of Things (IoT)-based misting system. The implementation methods included socialization, training, technology application, mentoring, and evaluation involving ten active farmers supported by BUMDes Dinaril. Program evaluation instruments consisted of observations, interviews, and IoT-based humidity sensor data. The data were analyzed descriptively and comparatively by comparing conditions before and after program implementation. The results showed an increase in productivity to approximately 40 kg per day, a reduction in baglog damage rates from approximately 20% to less than 5%, and more stable mushroom house humidity within the range of 80–90%. In addition, the harvest of the farmer group can now be distributed through the Merah Putih Cooperative under the MBG program. The program proved capable of increasing the group’s income by approximately IDR 3–4 million per month and strengthening member participation in business management. This program demonstrates that the integration of appropriate technology and the strengthening of local institutions are effective in sustainably improving farmers’ welfare.